Mangrove spatial heterogeneity as an inorganic pollutants’ ecological indicator - Ramya, Razanah; Othman, Rashidi; Mohd Hatta, Farah Ayuni; Mohd Latiff, Nur Hanie; Wan Sulaiman, Wan Syibrah Hanisah (Nova Science Publishers, Inc., 2024)
Between 1990 and 2020, the global mangrove coverage shrunk by 1.04 million ha. Over the course of three decades, the annual loss rate decreased from 46700 hectares in 1990–2000 to 36300 ha in 2000–2010. Southeast Asia has roughly 33.5% of the world’s mangroves, followed by South America (15.7%), North and Central America (14.7%), and West and Central Africa (13.2% of mangroves). Malaysia’s mangrove environment is the sixth largest in the world, behind Indonesia, Australia, Brazil, Nigeria, and Mexico. Peninsular Malaysia (17%), Sabah (58.6%), and Sarawak (24.4%) make up about 3.7% (577, 558 ha) of the world’s mangrove distribution. The main goal of this study is to ascertain threats and challenges to mangrove ecosystems around the world, especially in Malaysia, as well as the ecological significance of mangroves, their capability for phytoremediation of heavy metal pollution, their potential for use as a phytoindicator in coastal regions, and their capacity to tolerate heavy metals. The study also intends to offer suggestions for sustaining mangroves to ecologists, academic, agencies and other stakeholders. Mangroves have been degraded and cleared for human use in the majority of nations, mostly to support farming, aquaculture, and infrastructure growth. Notably, the discharge of inorganic pollutants such as phosphorus, nitrogen, and heavy metals into the ecosystem as a result of improperly managed aquaculture waste disposal has impacted mangrove areas. As a result, pollutants from catchments may be absorbed by mangrove sediments. Metal-contaminated soils can be cleaned up using physical, chemical, or biological methods. However, they are typically costly, may permanently harm soil properties, and could make soil useless as a substrate for plant growth. Research is being done on new, environmentally friendly technologies such as phytoremediation as potential substitutes.